Evaluasi Kebijakan: Pembangunan Desa melalui Energi Terbarukan (Studi Kasus Pembangkit Listrik Tenaga Surya di Desa Rawasari, Jambi) - Ahmad Rahma Wardhana; Wening Hapsari Ma'rifatullah (Universitas Batanghari Jambi, 2019)
Fossil energy (petroleum, coal, natural gas) is a double-edged sword; on the one hand its energy is fuel for development, but on the other hand, its residue contributes to global warming and climate change. Renewable energy as an antithesis of fossil energy is an alternative to answer the problem of the use of fossil energy that is considered unfriendly to the earth. Indonesia as an archipelagic country has an abundance of renewable energy resources that are ready to develop its potential to implement environmentally sensitive development policies. In 2016, LAKPESDAM-PBNU, Center for Energy Studies UGM, Center for Economic Democratic Studies, and Center for Civic Engagement Studies had the opportunity to develop renewable energy systems in three locations, one of which is Rawasari Village, in Jambi. This paper aims to provide an evaluation of the energy system development policy which contains an overview of the dynamics, opportunities, and challenges of the implementation of renewable energy to encourage energy diversification and independence as part of supporting Indonesia's development from the villages.